Comparative Study of Solubility of Urinary Stones in Juices of Different Common Edible Natural (Fruits) Sources - Rani Sinha, Madhu; Tagore, R.N. (Asian Journal of Chemistry, 2010)
Renal calculi are in general hard to break and the hardness varies from stone to stone depending on their constituents and size. Risks of renal stone formation are much fold increase in acidic medium rather than in alkaline medium. Foods that are high in citrate content generally are assumed to deliver alkali load and hence reduce the risk of stone formation. The object of this study is to compare the solubility properties of renal calculi of different forms and size (whole and powdered) in juices of three different common edible fruits i.e. apple (Malus domestica), moushmi (Citrus medica) and amla (Emblica officinalis). All reactions were carried out at room temperature (15 ºC) and pressure (738 mm of Hg) in vitro for 48 and 72 h. Attempts have been made to solubilize the whole stone and powdered stone by treating them with juices of different fruits for 48 and 72 h. This comparative study showed that the solubility of renal stone ingredients of smaller size stone was more than bigger sized stone and powdered form was much more than the whole stone. The dissolving properties of moushmi juice was compa-ratively much more than apple and amla juice. Apple juice had least dissolving effect. This short-term study suggests that moushmi juice would be helpful in designing of herbal preparation for dissolving, at least partially 'the urinary stones', however, additional studies are needed to evaluate the role of such kinds of fruit's juice in long-term preventive and therapeutic management of nephrolithiasis.